Characteristics of Pathological Fluor Albus on Outpatient in Permata Serdang Mother and Child Hospital Year 2019 - Monintja, Hans Eldith; Anandani, Adinta (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2020)
Background: Based on Indonesia Ministry of Health in 2010, about 75% of woman ever had a vaginal discharge at least once in a lifetime and 45% of woman had vaginal discharge twice or more. The most common risk factor that causing pathological fluor albus is genital organ hygiene. Purposes: The objective of this study is to determine the characteristics of pathological fluor albus on outpatient in RSIA Permata Serdang in 2019. Methods: This was an observational study based on medical record samples in 74 patients with pathological fluor albus between January 2019 and December 2019. Results: From 74 patients with pathological fluor albus, the highest age range occurred 25-29 years age category (24.3%), with the most marital status was married (97.3%), and the most dominant occupation was housewife (51.4%) and mostly living in Serang (52.7%). Clinical manifestations were itching and odor (28.4%), itching (27%), itching with pain and odor (14.9%), odor (10.8%). The secret color is clear (86.5%) followed by white-coloured secret (13.5%). Physical examination have been done with speculum examination (77%). Management provided for the patients are metronidazole (86.5%) and fluconazole (13.5%). Conclusion: Pathological fluor albus at RSIA Permata Serdang occurs often aged 25-29 years in a married woman with the common characteristic complaint was itching with odor.